High-Purity and Clean Syngas and Hydrogen Production From Two-Step CH4 Reforming and H2O Splitting Through Isothermal Ceria Redox Cycle Using Concentrated Sunlight - Chuayboon, Srirat; Abanades, Stéphane; Rodat, Sylvain (Frontiers in Energy Research, 2020)
The thermochemical conversion of methane (CH4) and water (H2O) to syngas and hydrogen, via chemical looping using concentrated sunlight as a sustainable source of process heat, attracts considerable attention. It is likewise a means of storing intermittent solar energy into chemical fuels. In this study, solar chemical looping reforming of CH4 and H2O splitting over non-stoichiometric ceria (CeO2/CeO2−δ) redox cycle were experimentally investigated in a volumetric solar reactor prototype. The cycle consists of (i) the endothermic partial oxidation of CH4 and the simultaneous reduction of ceria and (ii) the subsequent exothermic splitting of H2O and the simultaneous oxidation of the reduced ceria under isothermal operation at 1,000°C, enabling the elimination of sensible heat losses as compared to non-isothermal thermochemical cycles. Ceria-based reticulated porous ceramics with different sintering temperatures (1,000 and 1,400°C) were employed as oxygen carriers and tested with different methane flow rates (0.1–0.4 NL/min) and methane concentrations (50 and 100%). The impacts of operating conditions on the foam-averaged oxygen non-stoichiometry (reduction extent, δ), syngas yield, methane conversion, solar-to-fuel energy conversion efficiency as well as the effects of transient solar conditions were demonstrated and emphasized. As a result, clean syngas was successfully produced with H2/CO ratios approaching 2 during the first reduction step, while high-purity H2 was subsequently generated during the oxidation step. Increasing methane flow rate and CH4 concentration promoted syngas yields up to 8.51 mmol/gCeO2 and δ up to 0.38, at the expense of enhanced methane cracking reaction and reduced CH4 conversion. Solar-to-fuel energy conversion efficiency, namely, the ratio of the calorific value of produced syngas to the total energy input (solar power and calorific value of converted methane), and CH4 conversion were achieved in the range of 2.9–5.6% and 40.1–68.5%, respectively.